Characterization of protein-protein interactions underlying liquid-liquid phase separation in Rubisco biomolecular condensates - Poh, Cheng Wei (Nanyang Technological University, 2025)
As the gateway enzyme responsible for the assimilation of virtually all inorganic carbon into the biosphere, Rubisco is infamous for its slow and promiscuous activity. To compensate for its shortcomings, many marine phytoplanktons have evolved biophysical CO2 concentrating mechanisms (CCM) to increase the local CO2 concentration around Rubisco, thereby increasing carboxylation efficiency via mass action kinetics. At the core of these biophysical CCMs is a Rubisco-dense membraneless organelle known as the pyrenoid which assembles via liquid-liquid phase separation (LLPS). Here, we focused on the characterization of the red-type pyrenoid of the diatom Phaeodactylum tricornutum. The assembly of the P. tricornutum pyrenoid is driven by multivalent interactions between P. tricornutum Rubisco (PtRubisco) and the Rubisco linker protein Pyrenoid Component 1 (PYCO1). The structural basis of these interactions was revealed to be between PYCO1 ‘KWSPRGGS’ motifs and PtRubisco small subunits and between PYCO1 ‘AAEWGSMNQ’ motifs and PtRubisco large subunits. In this study, the general principles of PYCO1-PtRubisco heterotypic LLPS were elucidated. Within PtRubisco-dense heterotypic condensates, PtRubisco and PYCO1 contribute towards scaffolding of the internal matrix. The interplay between homotypic and heterotypic interactions, which varies with the stoichiometry of dense phase components, determines the liquid dynamics of heterotypic condensates. From systematic analysis of PYCO1 truncations, variability between PYCO1 repeat sequences were revealed to modulate the propensity of adjacent repeats to interlink Rubiscos. In addition, homotypic interactions were demonstrated to be essential for driving heterotypic LLPS. The molecular basis of PYCO1 homotypic LLPS is governed by two opposing forces: electrostatic repulsion between positively charged residues and the π-π interactions between aromatic residues. In the search for additional PtRubisco linker proteins, Glove1, Glove2 and PYCO2 were identified. Glove1 and Glove2 were characterized to be Rubisco linker proteins that are functionally distinct from PYCO1 while PYCO2 was determined to be a modulator of PYCO1-PtRubisco heterotypic LLPS. The findings of this study will contribute towards ongoing efforts that aim to engineer biophysical CCMs into C3 crop plants.